Epidemiological investigation and pathogenicity analysis of waterfowl astroviruses in some areas of China - Li, Yang; Luo, Juan; Shang, Jiajing; Zhang, Fuyou; Deng, Chunran; Feng, Yingjie; Meng, Ge; Jiang, Wenming; Yu, Xiaohui; Liu, Hualei (Frontiers in Microbiology, 2024)
Waterfowl astroviruses are mainly duck astroviruses and goose astroviruses, of which duck astroviruses (DAstV-3, -4), goose astroviruses (GoAstV-1, -2) are the four new waterfowl astroviruses in recent years, which can lead to enteritis, viral hepatitis, gout and reduce the growth performance of waterfowl, affecting the healthy development of the waterfowl farming industry. Since no targeted drugs or vaccines on the market, studies on the epidemiology of the virus are necessary for vaccine development. In this study, we collected 1546 waterfowl samples from 13 provinces in China. The results showed that 260 samples (16.8%) were positive. Four species of astrovirus were detected in 13 provinces except Fujian province. Among the four sites tested, the highest positive rates were found in farms and slaughterhouses. Cross-host and mixed infection were observed in four species of waterfowl astroviruses. The whole genome of 17 isolates was sequenced and compared with published sequences. Genetic evolution and homology analysis showed that the isolated strains had high similarity to their reference sequences. To assess the pathogenicity of GoAstV, 7-day-old goslings were inoculated with GoAstV-1 and GoAstV-2 by the intramuscular route, and infected geese showed similar clinical signs, such as anorexia, depression, and weight loss. Organ damage was seen after infection, with histopathological changes in the heart, liver, spleen, kidney, and intestine, and higher viral loads in throat and anal swabs. These findings increase our understanding of the pathogenicity of GoAstV-1 and GoAstV-2 in goslings and provide more reference for future research.